Synthesis and characterization of oxime-bearing hexakis(2-formylphenoxy)-phosphazene and its derivatives - Pamukci, Orhan; Cil, Erol; Begec, Saliha; Arslan, Mustafa (John Wiley & Sons Inc, 2007)
Hexakis (2-formylphenoxy)cyclotrlphosphazene (2) was obtained from the reaction of hexachlorocylotriphosphazene (1) with 2-hydroxybenzaldehyde. Hexakis (2-[(hydroxyimino) methyl]phenoxy)cyclotriphosphazene (3) was synthesized from the reaction of 2 with hydroxlaminehydrochloride in pyridine. Hexasubstituted compounds 4, 5, 6, 8, 9, and 10 were obtained from the reactions of 3 with methyl iodide, ethyl bromide, allyl bromide, propanoyl chloride, benzoyl chloride, and 4-methoxybenzoyl chloride, respectively. Disubstituted product 7 was obtained from the reaction of 3 with chloroacetyl chloride. Pure and defined products could not be obtained from the reaction of 3 with acetyl chloride, benzyl chloride, and 2-chlorobenzoyl chloride. The compounds were characterized by elemental analysis and IR, H-1, C-13, and P-31 NMR spectroscopy. (c) 2007 Wiley Periodicals, Inc.
Keywords: Dichlorophosphoryl-P-Trichlorophosphazene; Phosphazene High Polymers; Linear Phosphazenes; Nitrile Spacer; Yeast-Cells; Cyclotriphosphazene; Cyclophosphazenes; Bacterial; Alkyl; Hexachlorocyclotriphosphazatriene